XRF analysis of Gotlandic box brooch data set - Thuresson, Kaj (Swedish National Heritage Board, 2022)
XRF analasis of Gotlandic box brooch, performed in order to evaluate the material, composition of alloy, and where there are different areas of silver. The information is valuable when conservating the object and cleaning up original surfaces. Results show that brooch is multi coloured with brass, bronze and silver.

Raw data set in .rtx format. ARTAX soft ware will be needed to open files.
Keywords: History and Archaeology; Historia och arkeologi